Occult HBV infection in patients with autoimmune hepatitis: A virological and clinical study - Xin-Xin Chen; Kuan-Hui Xiang; Hai-Ping Zhang; Xiang-Sha Kong; Chun-Yang Huang; Yan-Min Liu; Jin-Li Lou; Zu-Hua Gao; Hui-Ping Yan (J Microbiol Immunol Infect ., 2020)
Background/purpose: Occult HBV infection (OBI) could have serious clinical consequences in patients receiving immunosuppressive therapy. We aimed to investigate the prevalence of OBI in Chinese patients with autoimmune hepatitis (AIH) and to analyze its clinical and virological features. Methods: 103 AIH cases were enrolled. Hepatitis B virus (HBV) serological markers were screened by chemiluminescence. HBV-DNA were detected by nest-PCR and real-time PCR. HBV genotyping and mutation analysis were performed by Sanger sequencing. Results: Twenty-four out of 103 (23.30%) AIH patients had OBI as evidenced by positive HBV-DNA and negative hepatitis B surface antigen (HBsAg). HBV genotype C is the predominant genotype (57.89%), which had more amino acid (AA) substitutions in S region than that of B-genotype group (P = 0.001). The distribution of AA substitution in the 'α' determinant region between genotype C and B were significantly different (P = 0.042). In addition to those already reported OBI-associated AA substitutions (e.g., sG145R and sV184A), some new OBI-associated AA substitutions (e.g., sV106A, sC137* and sL176P) were found in AIH patients in our study. Three out of 24 (12.50%) OBI patients were diagnosed as decompensated cirrhosis, one patient with S deletion mutation and two patients with HBV extensive AA substitutions. Conclusions: There was a higher proportion of AIH patients with OBI than the general population in China, which can be either seropositive or seronegative-OBI in AIH patients is associated with some specific AA substitutions. The presence of deletion mutations and the extent of AA substitutions in the HBV S region may have predictive clinical implications. Keywords: Amino acid substitution; Autoimmune hepatitis; Occult HBV infection.